Penalties and Rewards in Islamic Religious Education - Fauziyah, Annisa Shivia; Nurjanah, Dedeh; Nurparid, Cucu; Mastuhi, Mastuhi (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study is to analyze the methods of punishment and reward in Islamic religious education. The qualitative research method was used in this study.Qualitative research is a type of research that produces findings that cannot be achieved by using statistical procedures or other means of quantification. The results of the research show that targhib-tarhib is a strategy or way to convince someone of the truth of Allah SWT through His promise to do good deeds in the form of enjoyment in the afterlife and threats for those who disobey Him. This method includes giving lessons by giving encouragement (motivation) to get joy if you get success in goodness, while if you don’t succeed because you don’t want to follow the right instructions, you will get into trouble.